(untitled) (International Journal of World Civilizations and Philosophical Studies, 2025)
Bias is often perceived as a challenge to objectivity in every field of knowledge, including history. The problem of bias in history has received special attention from historians since the late 19th and early 20th centuries. Notably, the topic also involves discussions on moral judgments in historiography, as if the two are strongly related. Some historians have argued that moral judgment in historiography leads to biased history and should be avoided. On the other hand, others contend that moral judgment in historiography should not be prohibited merely because it introduces bias, as there can be both justified and unjustified bias. Hence, this paper aims to present the issue of moral judgment in historiography as a cause of biased history and to explain why this issue does not necessarily undermine the legitimacy of moral judgment in historiography. As a philosophical study, the research will employ content analysis and logical inference using library-based sources to shed light on the issue. The study indicates that fundamentally, abandoning moral judgment to avoid biased history reflects a flawed understanding of the philosophy of historiography and is practically untenable.